Food Safety Challenges towards Safe, Healthy, and Nutritious Street Foods in Bangladesh - Md. Khairuzzaman; Fatema Moni Chowdhury; Sharmin Zaman; Arafat Al Mamun; Md. Latiful Bari (International Journal of Food Science)
The street foods play an important socioeconomic role in meeting food and nutritional requirements of city consumers at affordable prices to the lower and middle income people. The number of food poisoning notifications rose steadily worldwide since the inception of E. coli O157:H7 outbreak in the 1980s to date. This may be partly attributed to improved surveillance, increased global trade and travel, changes in modern food production, the impact of modern lifestyles, changes in food consumption, and the emergence of new pathogens. Consumer’s knowledge and attitude may influence food safety behavior and practice. For the sake of public health, it is important to understand the epidemiology of foodborne illnesses that help in prevention and control efforts, appropriately allocating resources to control foodborne illness, monitoring and evaluation of food safety measures, development of new food safety standards, and assessment of the cost-effectiveness of interventions. This review paper described the sociodemographic characteristics, common hazards, and occupational hazards of street food vendors, microbial risk associated with street food, food safety interventions and control measures, regulatory aspects and legal requirements, financial constraints, and attitudes.